A New Dietary Therapy for Chronic Renal Failure: Intestinal Dialysis Technology - Aamir Jalal Al Mosawi (Journal of Medical and Surgical Urology, 2020)
A new dietary approach used to lower urea levels in chronic renal failure, and thus simulating dialysis has been recently described. This approach has been increasingly called intestinal or dietary dialysis. The aim of this paper is to describe the emerging evidence, principles, and concepts related to intestinal dialysis.
Keywords: chronic renal failure